2019
DOI: 10.1016/j.econmod.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Self-employment and the Okun's law

Abstract: The present research provides evidence on the determinants driving the differences in the unemploymentoutput relationship in Spanish regions. We followed a two-step approach. First, we estimated a set of time-varying Okun's coefficients (rolling-window) for the autonomous communities in Spain (1981-2013) showing significant regional differences as well as important changes over time. At the second step, we estimated FMOLS and DOLS models to explain regional differences in Okun's law. The results obtained lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 51 publications
1
7
0
4
Order By: Relevance
“…Studies at the regional level, for other countries with similar experiences during the crisis (mainly, Spain), have also highlighted structural issues as key determinants for the Okun Law elasticity. For example, Melguizo (2017) has shown the unemployment elasticity to be higher for Spanish provinces with less diversified industries and greater specialization in services; while, for the same country, Bande and Martín-Román (2018) and Porras-Arena and Martin-Roman (2019) provided evidence of heterogeneity in the Okun coefficient at the regional level. 2…”
Section: Introductionmentioning
confidence: 99%
“…Studies at the regional level, for other countries with similar experiences during the crisis (mainly, Spain), have also highlighted structural issues as key determinants for the Okun Law elasticity. For example, Melguizo (2017) has shown the unemployment elasticity to be higher for Spanish provinces with less diversified industries and greater specialization in services; while, for the same country, Bande and Martín-Román (2018) and Porras-Arena and Martin-Roman (2019) provided evidence of heterogeneity in the Okun coefficient at the regional level. 2…”
Section: Introductionmentioning
confidence: 99%
“…E.g. seePorras-Arena and Martín-Román, 2019;Guisinger et al, 2018;Durech et al, 2014;Freeman, 2000;Bande and Martin-Roman, 2018;Villaverde and Maza, 2009 for regional differences and Evans, 2018 for demographic differences Abe and Ohta (2001). investigate Japan and Hartwig (2014) study Switzerland at the sector level and found large differences across sectors.2 E.g.…”
mentioning
confidence: 99%
“…Nevertheless, neither the theoretical setting nor the empirical strategy is the same as ours. Moreover, the aim of their investigation differs from ours.4 See, for instance,Martín-Román, Moral de Blas & Martínez-Matute (2015).5 In this vein,Ball, Leigh, and Loungani (2017),, and Porras-Arena andMartín-Román (2019) have provided empirical evidence of the large size of the Spanish business cycle, particularly with regard to the labour market outcomes.6 The 50 Spanish provinces correspond to the third level (NUTS 3) of the Nomenclature of Territorial Units for statistics, see: http://ec.europa.eu/eurostat/ web/nuts/overview.…”
mentioning
confidence: 72%
“…Finalmente, el tercero de los motivos se basa en la elevada sensibilidad cíclica observada en algunas de las variables más importantes del mercado laboral español. Es bien sabido que el caso español se caracteriza por la existencia de ciclos económicos amplios y por el efecto que este ejerce sobre la propia tasa de desempleo en forma de una notable creación de empleo durante los periodos de expansión económica y por una gran destrucción del mismo durante las etapas de recesión (Ball et al, 2019;Bande y Martín-Román, 2018; Porras-Arena y Martín-Román, 2019).…”
Section: Justificación Y Objetivos De La Investigaciónunclassified
See 1 more Smart Citation